Effects of warm-up on hamstring muscles stiffness: Cycling vs foam rolling - Morales-Artacho, A. J.; Lacourpaille, L.; Guilhem, G. (Scandinavian Journal of Medicine & Science in Sports, 2017)
This study investigated the effects of active and/or passive warm-up tasks on the hamstring muscles stiffness through elastography and passive torque measurements. On separate occasions, fourteen males randomly completed four warm-up protocols comprising Control, Cycling, Foam rolling, or Cycling plus Foam rolling (Mixed). The stiffness of the hamstring muscles was assessed through shear wave elastography, along with the passive torque-angle relationship and maximal range of motion (ROM) before, 5, and 30 minutes after each experimental condition. At 5 minutes, Cycling and Mixed decreased shear modulus (-10.3% ± 5.9% and -7.7% ± 8.4%, respectively; P=.0003, effect size [ES]=0.24) and passive torque (-7.17% ± 8.6% and -6.2% ± 7.5%, respectively; P=.051, ES=0.28), and increased ROM (+2.9% ± 2.9% and +3.2% ± 3.5%, respectively; P=.001, ES=0.30); 30 minutes following Mixed, shear modulus (P=.001, ES=0.21) and passive torque (P=.068, ES=0.2) were still slightly decreased, while ROM increased (P=.046, ES=0.24). Foam rolling induced "small" immediate short-term decreases in shear modulus (-5.4% ± 5.7% at 5 minutes; P=.05, ES=0.21), without meaningful changes in passive torque or ROM at any time point (P=.12, ES=0.23). These results suggest that the combined warm-up elicited no acute superior effects on muscle stiffness compared with cycling, providing evidence for the key role of active warm-up to reduce muscle stiffness. The time between warm-up and competition should be considered when optimizing the effects on muscle stiffness.